Development of Mechanical Engineering in the Conditions of Globalization (Experience of EU Countries) - Sozanskyy, L. Yo. (Statistics of Ukraine, 2023)
The study was carried out with the aim of evaluating and substantiating the key systemic problems of the functioning of the national engineering industry of various countries in the conditions of economic globalization. In order to achieve the goal, development trends and key relative indicators of Polish and German mechanical engineering were analyzed during and under the influence of increased economic globalization. It is analytically substantiated that during the period of economic globalization, absolute indicators increased, in particular the volume of production and the number of employees of the Polish mechanical engineering industry, but instead, its innovativeness and technology decreased significantly, and dependence on foreign enterprises increased. It was revealed that the German engineering industry, in particular the automobile industry, has undergone significant destructive changes under the influence of increased economic globalization. First of all, this is a tendency to decrease the number of cars, and a significant decrease in the share of innovative products in the volume of sold industrial products of the production of motor vehicles, trailers and semi-trailers. It is concluded that the identified destructive changes are the result of an irrational, one-sided perception of economic globalization by the main business entities of these countries. In particular, this is the failure to take into account the systemic effects of foreign enterprises and TNCs, excessive export-orientation of products, offshoring, auto-sourcing on the activities of mechanical engineering and the socio-economic development of countries in general. The obtained results of the study became the basis for the formation and analytical and theoretical-philosophical substantiation of the hypothesis that compliance with a high level of provision of production processes by national, not controlled from the outside, products of intermediate consumption and an optimal level of export-orientation of machine-building industries, along with a decrease in the level of monopolization in high-tech segments of the global economy, in the long term, will contribute to the satisfaction of the interests of both national economies (in particular, entrepreneurship and the social sphere), and TNCs.